Thermal fatigue and corrosion fatigue in heat recovery area wall side tubes - Ahmad J.; Purbolaksono J.; Beng L.C. (2023)
In this paper, findings of visual inspections, chemical analysis on deposits, metallurgical examinations and creep analysis on the failed SA210-A1 heat recovery area (HRA) wall side tubes of a boiler unit are presented. The investigations were carried out following two boiler tube failures at heat recovery areas involving the left hand side (LHS) and right hand side (RHS) side wall tubes. Findings from the microscopic examinations are used to support the investigation in determining the failure mechanisms. The first failure at LHS HRA side wall tube is identified due to thermal fatigue while the second failure is as a result of combination of the corrosion fatigue, thermal fatigue and creep damage. Recommendations are made to reduce unavailability of the boiler unit due to the HRA side wall tube failures. 2009 Elsevier Ltd. All rights reserved.